Biomechanical analysis of anterior cruciate ligament injury mechanisms: three-dimensional motion reconstruction from video sequences - Krosshaug, T.; Slauterbeck, J. R.; Engebretsen, L.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2006)
Background: Methods for analyzing the mechanisms of injuries in sports from video sequences of injury situations are so far limited to a simple visual inspection, which has shown poor accuracy.